The Effect of Saturated Fatty Acids on Methanogenesis and Cell Viability of Methanobrevibacter ruminantium. (28th April 2013) - Zhou, Xuan; Meile, Leo; Kreuzer, Michael; Zeitz, Johanna O.
Abstract : Saturated fatty acids (SFAs) are known to suppress ruminal methanogenesis, but the underlying mechanisms are not well known. In the present study, inhibition of methane formation, cell membrane permeability (potassium efflux), and survival rate (LIVE/DEAD staining) of pure ruminal Methanobrevibacter ruminantium (DSM 1093) cell suspensions were tested for a number of SFAs. Methane production rate was not influenced by low concentrations of lauric (C12 ; 1 μ g/mL), myristic (C14 ; 1 and 5 μ g/mL), or palmitic (C16 ; 3 and 5 μ g/mL) acids, while higher concentrations were inhibitory. C12 and C14 were most inhibitory. Stearic acid (C18 ), tested at 10–80 μ g/mL and ineffective at 37°C, decreased methane production rate by half or more at 50°C and ≥50 μ g/mL. Potassium efflux was triggered by SFAs (C12 = C14 > C16 > C18 = control), corroborating data on methane inhibition. Moreover, the exposure to C12 and C14 decreased cell viability to close to zero, while 40% of control cells remained alive after 24 h. Generally, tested SFAs inhibited methanogenesis, increased cell membrane permeability, and decreased survival of M. ruminantium in a dose- and time-dependent way. These results give new insights into how the methane suppressing effect of SFAs could be mediated in methanogens.